The immunoglobulin heavy chain enhancer is stimulated by the adenovirus type 2 E1A products in mouse fibroblasts. - Borrelli, E (1986)
In contrast with our previous results (Hen, R., Borrelli, E. & Chambon, P. (1985) Science 230, 1391-1394), which demonstrated that the mouse immunoglobulin heavy chain transcriptional enhancer is repressed in lymphoid cells by the products of the adenovirus type 2 E1A transcription unit, we show here that these products activate the same enhancer in mouse fibroblast L cell lines that contain stably integrated copies of a recombinant in which the enhancer is inserted upstream from the chicken conalbumin promoter. In addition, competition experiments suggest that the activity of the heavy chain enhancer may be repressed by a trans-acting factor in mouse L cells. We speculate that the E1A products may prevent the action of this cellular repressor in these cells.